Visualization of nanoscale magnetic domain states in the asteroid Ryugu - Yuki Kimura; Takeharu Kato; Toshiaki Tanigaki; Tetsuya Akashi; Hiroto Kasai; Satoshi Anada; Ryuji Yoshida; Kazuo Yamamoto; Tomoki Nakamura; Masahiko Sato; Kana Amano; Mizuha Kikuiri; et al. (Scientific Reports, 2023)
Abstract In the samples collected from the asteroid Ryugu, magnetite displays natural remanent magnetization due to nebular magnetic field, whereas contemporaneously grown iron sulfide does not display stable remanent magnetization. To clarify this counterintuitive feature, we observed their nanoscale magnetic domain structures using electron holography and found that framboidal magnetites have an external magnetic field of 300 A m−1, similar to the bulk value, and its magnetic stability was enhanced by interactions with neighboring magnetites, permitting a disk magnetic field to be recorded. Micrometer-sized pyrrhotite showed a multidomain magnetic structure that was unable to retain natural remanent magnetization over a long time due to short relaxation time of magnetic-domain-wall movement, whereas submicron-sized sulfides formed a nonmagnetic phase. These results show that both magnetite and sulfide could have formed simultaneously during the aqueous alteration in the parent body of the asteroid Ryugu.